2022
DOI: 10.1111/cpr.13193
|View full text |Cite
|
Sign up to set email alerts
|

Roles of necroptosis in alcoholic liver disease and hepatic pathogenesis

Abstract: Chronic alcohol consumption can cause alcoholic liver disease (ALD), leading to morbidity and mortality worldwide. Complex disease progression of ALD varies from alcoholic fatty liver to alcoholic steatohepatitis, eventually contributing to fibrosis and cirrhosis. Accumulating evidence revealed that necroptosis, a way of programmed cell death different from apoptosis and traditional necrosis, is involved in the underlying pathogenic molecular mechanism of ALD. Receptor‐interacting protein kinase 1 (RIPK1), RIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 84 publications
(191 reference statements)
1
23
0
Order By: Relevance
“…Necroptosis is an important programmed cell death, which is characterized by the activation of MLKL/pMLKL by the RIPK1/RIPK3-mediated phosphorylation signal pathway ( Karlowitz and van Wijk 2021 ; Zhou et al, 2022 ). Recent studies have found that NRGs play a dual role in both facilitating and suppressing the progression of different tumor cells and could be used as prognostic and therapeutic biomarkers in patients with many types of tumors ( Pasparakis and Vandenabeele, 2015 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis is an important programmed cell death, which is characterized by the activation of MLKL/pMLKL by the RIPK1/RIPK3-mediated phosphorylation signal pathway ( Karlowitz and van Wijk 2021 ; Zhou et al, 2022 ). Recent studies have found that NRGs play a dual role in both facilitating and suppressing the progression of different tumor cells and could be used as prognostic and therapeutic biomarkers in patients with many types of tumors ( Pasparakis and Vandenabeele, 2015 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathways involved in PCD include the apoptosis, necroptosis, pyroptosis, autophagy, and ferroptosis pathways [ 19 ]. Apoptosis is a cystein-dependent cell death, and chronic alcohol intake induces oxidative stress, hypoxic stress, and endoplasmic reticulum stress in cells, leading to the activation of endogenous and exogenous apoptosis [ 20 , 21 ]. Cellular stress induces apoptosis in the liver by activating caspase-12/4, the interferon regulatory factor signalling pathway, and the C-Jun N-terminal kinase [ 22 ].…”
Section: Pathogenesis Of Aldmentioning
confidence: 99%
“…Ethanol exposure increases intestinal permeability and subsequent entry of LPS into the portal vein circulation, which stimulates resident hepatic macrophages, and infiltrates monocytes to produce inflammatory factors such as tumour necrosis factor -α(TNFα) through the activation of Toll-like receptor 4 (TLR4), thereby activating the exogenous pathway of apoptosis [ 22 ]. Necrosis is a novel form of PCD mediated by receptor-interacting protein kinase 1 (RIPK1), RIPK3, and mixed-lineage kinase domain-like pseudokinase (MLKL) [ 21 ]. Necrosis has been shown to play a key role in oxidative stress, steatosis, and inflammatory response in ALD [ 24 , 25 , 26 , 27 ].…”
Section: Pathogenesis Of Aldmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking culture is a worldwide phenomenon, but long-term alcohol consumption may lead to alcoholic fatty liver disease [ 1 ]. In addition to increasing the risk of chronic disease, excessive ethanol intake can cause acute unpleasant physiological and psychological effects, including hangover [ 2 ].…”
Section: Introductionmentioning
confidence: 99%